"Mischievous Uncles" as Rule Breakers: Intersectional Stereotypes and Risk Perceptions During the Coronavirus Pandemic in Turkey. (August 2020) - Türkoğlu, Didem; Odabaş, Meltem
Responses to crises can highlight and exacerbate class inequalities. Seemingly neutral policy measures taken during the COVID-19 pandemic that aim to protect high-risk groups can lead to a shift in the public discourse that deprives citizens of their agency based not only on their age but also their class. In this article, we focus on the case of Turkey, one of the countries with the fastest growth of novel coronavirus cases in late March 2020, where the government introduced a curfew for people over the age of 65, while actively encouraging the rest of the working-age population to stay at home. An intersectional analysis of the Twitter campaign #StayatHome (# EvdeKal ) and the media outlets' news coverage of the policy implementation show that both platforms circulated human-interest stories of working-class men who defy the curfew predominantly. Both the stories and Twitter user comments often defined the subjects of those stories as rule-breakers and, therefore, as "mischievous uncles." They became the scapegoats, while upper and middle classes avoided the label. These findings have implications for the framing of policy outcomes and welfare provisions as well as oppositional politics that push for the expansion of labor protections during the pandemic.